Responses of Aspergillus flavus to Oxidative Stress Are Related to Fungal Development Regulator, Antioxidant Enzyme, and Secondary Metabolite Biosynthetic Gene Expression - Fountain, Jake C.; Bajaj, Prasad; Nayak, Spurthi N.; Yang, Liming; Pandey, Manish K.; Kumar, Vinay; Jayale, Ashwin S.; Chitikineni, Anu; Lee, Robert D.; Kemerait, Robert C.; Varshney, Rajeev K.; Guo, Baozhu (Frontiers in Microbiology, 2016)
The infection of maize and peanut with Aspergillus flavus and subsequent contamination with aflatoxin pose a threat to global food safety and human health, and is exacerbated by drought stress. Drought stress-responding compounds such as reactive oxygen species (ROS) are associated with fungal stress responsive signaling and secondary metabolite production, and can stimulate the production of aflatoxin by A. flavus in vitro. These secondary metabolites have been shown to possess diverse functions in soil-borne fungi including antibiosis, competitive inhibition of other microbes, and abiotic stress alleviation. Previously, we observed that isolates of A. flavus showed differences in oxidative stress tolerance which correlated with their aflatoxin production capabilities. In order to better understand these isolate-specific oxidative stress responses, we examined the transcriptional responses of field isolates of A. flavus with varying levels of aflatoxin production (NRRL3357, AF13, and Tox4) to H2O2-induced oxidative stress using an RNA sequencing approach. These isolates were cultured in an aflatoxin-production conducive medium amended with various levels of H2O2. Whole transcriptomes were sequenced using an Illumina HiSeq platform with an average of 40.43 million filtered paired-end reads generated for each sample. The obtained transcriptomes were then used for differential expression, gene ontology, pathway, and co-expression analyses. Isolates which produced higher levels of aflatoxin tended to exhibit fewer differentially expressed genes than isolates with lower levels of production. Genes found to be differentially expressed in response to increasing oxidative stress included antioxidant enzymes, primary metabolism components, antibiosis-related genes, and secondary metabolite biosynthetic components specifically for aflatoxin, aflatrem, and kojic acid. The expression of fungal development-related genes including aminobenzoate degradation genes and conidiation regulators were found to be regulated in response to increasing stress. Aflatoxin biosynthetic genes and antioxidant enzyme genes were also found to be co-expressed and highly correlated with fungal biomass under stress. This suggests that these secondary metabolites may be produced as part of coordinated oxidative stress responses in A. flavus along with antioxidant enzyme gene expression and developmental regulation.